Doctoral dissertation in supply chain management research: a comprehensive review from 1999 to 2006. (10th February 2009) - Zhang, Xinrui; Yang, Jiaqin; Wang, Hengshan
Supply Chain Management (SCM), as a new managing approach has attracted a significant attention from both academic and industrial world. Integrating with the most recent advanced management models and IT technologies, the SCM research in the higher education of China has been also advanced extensively since 1990s. Reflecting this trend in SCM research, it has also seen a dramatic increase in selecting SCM-related research issues as research topic among recent Chinese university PhD dissertations. This paper presents a comprehensive review about recent Chinese SCM doctoral dissertation studies during the last decade along with managerial implications learned from the proposed multi-dimensional analysis.